INCREASING BEGINNING TEACHER EFFICACY & RETENTION IN A DIVERSE MIDDLE SCHOOL SETTING WITH APPROPRIATE PROFESSIONAL LEARNING - Neal, Keith Louis (East Carolina University)
Teacher retention, particularly among beginning educators, remains a pressing concern in education, especially in Title I middle schools that serve diverse student populations. High teacher attrition rates negatively impact student achievement, school culture, and overall educational equity. This study examines the role of targeted professional learning in increasing beginning teacher efficacy and retention in a rural North Carolina middle school. Through an exploratory sequential mixed methods approach, qualitative data were collected through interviews, classroom observations, and instructional rounds, followed by quantitative analysis utilizing pre- and post-surveys to measure changes in teacher confidence and instructional effectiveness. The findings reveal that relevant, structured, and ongoing professional learning opportunities significantly enhance teacher efficacy by providing educators with the tools and strategies necessary to navigate the challenges of their early careers. Key themes that emerged from the study include the importance of classroom management training, content-specific instructional strategies, culturally responsive pedagogy, and mentorship programs. Teachers who received professional learning tailored to their individual needs reported increased confidence in their instructional delivery, greater job satisfaction, and a stronger sense of belonging within the school community. Additionally, opportunities for collaboration, reflection, and leadership development played a pivotal role in sustaining teacher engagement and reducing burnout. Despite its contributions, this study acknowledges certain limitations, including the relatively small sample size and its focus on a single school setting. However, the findings offer meaningful insights into the design and implementation of effective professional learning programs that can support beginning teachers in similar educational contexts. Future research should explore the long-term impact of professional learning on teacher retention rates across multiple school districts and investigate its direct correlation to student achievement. By prioritizing intentional, sustained, and responsive professional development, school leaders can foster a culture of continuous learning, ultimately improving both teacher retention and student outcomes.
Keywords: Education, Educational Leadership